A qualitative process evaluation of social recovery therapy for enhancement of social recovery in first-episode psychosis (SUPEREDEN3). Issue 2 (13th March 2023) - Gee, Brioney; Berry, Clio; Hodgekins, Joanne; Greenwood, Kathryn; Fitzsimmons, Michael; Lavis, Anna; Notley, Caitlin; Pugh, Katherine; Birchwood, Max; Fowler, David
Abstract: Background: Many individuals with first-episode psychosis experience severe and persistent social disability despite receiving specialist early intervention. The SUPEREDEN3 trial assessed whether augmenting early intervention in psychosis services with Social Recovery Therapy (SRT) would lead to better social recovery. Aims: A qualitative process evaluation was conducted to explore implementation and mechanisms of SRT impact from the perspective of SUPEREDEN3 participants. Method: A subsample of SUPEREDEN3 trial participants ( n = 19) took part in semi-structured interviews, which were transcribed verbatim and analysed thematically. Trial participants were early intervention service users aged 16–35 years with severe and persistent social disability. Both SRT plus early intervention and early intervention alone arm participants were interviewed to facilitate better understanding of the context in which SRT was delivered and to aid identification of mechanisms specific to SRT. Results: The six themes identified were used to generate an explanatory model of SRT's enhancement of social recovery. Participant experiences highlight the importance of the therapist cultivating increased self-understanding and assertively encouraging clients to face feared situations in a way that is perceived as supportive, while managing ongoing symptoms. The sense of achievement generated by reaching targets linked to personally meaningful goals promotes increased self-agency, and generates hope and optimism. Conclusions: The findings suggest potentially important processes through which social recovery was enhanced in this trial, which will be valuable in ensuring the benefits observed can be replicated. Participant accounts provide hope that, with the right support, even clients who have persistent symptoms and the most severe disability can make a good social recovery.